Socio-cultural conditionality of social network development - Babosov, Yevgeni M. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The specifics of the network society are characterized, the socio-cultural conditionality of its emergence and development is revealed. It is emphasized that the purposefully working creative person is a creator of the network society, a driver of its development. Structural components of the network communication topology are explicated in theory.
Keywords: network society; socio-cultural conditionality; structural components of network topology; creative person